If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + x = -17 Solving 23 + x = -17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + x = -17 + -23 Combine like terms: 23 + -23 = 0 0 + x = -17 + -23 x = -17 + -23 Combine like terms: -17 + -23 = -40 x = -40 Simplifying x = -40
| n+(-2)=5 | | (x-y)(x^2-8xy+y^2)= | | -57+6x-2x=15 | | 2y-7y=20 | | 19x-24=27x | | y=(2/3)x-4 | | 3a+5ba+7a-2ba+11= | | 7x-3x-5=20 | | -4=-10-2e | | -3y+9=24x | | 25x^2+5x-25=0 | | 14x^2+35x-21=0 | | w-13=-8 | | 14x^2+35x-20=0 | | 3x-11=5x+9 | | 10x-10y=30 | | 36-4x=20+12x | | -14+s=50 | | 32x^2-5x-12=0 | | -8=-7/6(6)+b | | -(39x/51) | | 4x+20+2x+10=189 | | y-1=(x-6) | | 15x^2+5-[8(x^2-5)+9]= | | -7(t-7)-(t+8)=6 | | -123-6x+12x=45 | | 132=7x+7x+2 | | [2X+3]=9 | | -28=-8 | | 5(4z-1)-2(z+6)=16(z+1) | | 2(x+5)+4x=16 | | -x-118+10x=80 |